A study on assessing the benefits of homestay program among the homestay operators / Nurul Ain Ibrahim and Siti Nurulakmar Ismail - Ibrahim, Nurul Ain; Ismail, Siti Nurulakmar (Faculty of Hotel and Tourism Management, 2014)
Homestay program is one of the rural tourism products that highlight the Malaysian cultural and traditional ways of life. It has been introduced in 1988 and has been recognized as one of the economic engine that contributes to the local economy especially in the less developed areas. The purpose of this study is (l) to identify the determinants of participation background among the homestay operators and (2) to assess the benefits of homestay program among the homestay operators. The study will be conducted by using both primary and secondary resources. A total of 93, out of 115 homestay operators from seven different registered villages in Malacca were participated in this study. Primary data was collected by using self-administered questionnaire. From the study, the researchers identified the pattern of participation among the homestay operators in Malacca and classified the most significant benefits gained by participating in the homestay program which include economic benefits, standard of living and environmental balance. The result indicated that homestay program has benefited in terms of employment creation, business opportunities and extra income generation. The homestay program also has been proven to improve the operators' living standard, promote better awareness for the continued conservation of cultural heritage as well as maintaining the environmental balance.